Gender Construction in Islamic Perspective - Aditya Yuli Sulistyawan; Siti Sarah Nurfaidah (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
Gender issues are still a topic that is often discussed in society. Gender is related to the social construction of the division of activities between women and men. Along with the development of times there are many assumptions that say that women still accept injustice and are still discriminated against so that many are demanding gender equality for women. In the Qur'an many verses describe justice and equality between women and men in their responsibilities and carrying out their role, but there are still many people who do not understand the contents of the verses in question. The public or broad audience needs to understand gender construction in this Islamic perspective to be able to realize the ideal gender construction in life, especially in the context of Islamic society.